Primary prostatic lymphoma with components of both diffuse large B-cell lymphoma (DLBCL) and MALT lymphoma. - Petrakis, G (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2012)
Although lymphomas involving the prostate gland are rare, they should always be considered in the differential diagnosis. We report a case of primary prostatic NHL in a 70-year-old man presented with hematuria and urinary obstructive symptoms. Routine laboratory tests were within normal limits and prostate-specific antigen (PSA) was 0,01 ng/ml. The patient underwent radical prostatectomy. Histologically, two different coexisting patterns of non-Hodgkin lymphoma, infiltrating the prostatic tissue, were identified. The diagnosis of diffuse large B-cell lymphoma (DLBCL) presenting with an associated low-grade lymphoma of MALT-type was confirmed by immunohistochemistry. The patient received chemotherapy without any complication and has been followed-up for 2 years since surgical resection with no recurrence. The clinicopathologic characteristics of prostatic lymphomas are discussed, while reviewing the current English-language literature.